2(x - 5) = 4x - 2(x + 5) + 1

Asked 8 months ago
Viewed 502548 times
1
2(x - 5) = 4x - 2(x + 5) + 1

2 Answer

2

Answer:

0=1

Step-by-step explanation:

Edit
avatar
answered 8 months ago
2

Answer:

Step-by-step explanation:

Let's solve your equation step-by-step.

2(x−5)=4x−2(x+5)+1

Step 1: Simplify both sides of the equation.

2(x−5)=4x−2(x+5)+1

(2)(x)+(2)(−5)=4x+(−2)(x)+(−2)(5)+1(Distribute)

2x+−10=4x+−2x+−10+1

2x−10=(4x+−2x)+(−10+1)(Combine Like Terms)

2x−10=2x+−9

2x−10=2x−9

Step 2: Subtract 2x from both sides.

2x−10−2x=2x−9−2x

−10=−9

Step 3: Add 10 to both sides.

−10+10=−9+10

0=1

Answer:

There are no solutions.

Edit
avatar
Kaia Durgan IV
15.5k 3 10 26
answered 8 months ago